Bone Mineral Densitometry Findings of Children with Newly Diagnosed Celiac Disease - Balci, Tansel Ansal; Koc, Zehra Pinar; Mitil, Huseyin Aydin (Galenos Yayincilik, 2011)
Objective: The effect of Celiac Disease (CD) on children's bone is the decrease in bone mineral density (BMD). Osteoporosis is a consequence of this decrease and usually manifests in adult ages. Studies in CD patients generally show that bone density of these patients can be different at the same ages for the same duration of disease. The aim of this study is to investigate the relationship between age and bone mineral density of CD patients at first diagnosis. Material and Methods: Ninety one patients (M/F: 36/55; age range: 3-16; mean age: 9.6 +/- 3.5) with diagnosis of CD were included in the study. BMD survey from L1-L4 lumbar spine and total hip of the patients was evaluated at presentation. We evaluated the patients in 3 groups according to their ages: Group 1: pre-school (3-7 years old), Group 2: elementary school (8-11 years old) and Group 3: adolescent (12-16 years old). Results were compared using Student's t test and correlation analysis. Results: The mean disease duration of the patients was 16.4 +/- 16.3 months. Mean height and weight of the patients were 124.8 +/- 17.9 cm and 27 +/- 9.3 kg, respectively and height and weight of 37 patients were in = 3. percentile according to age. The BMD values of both lumbar spine and total hip and Z-scores of lumbar region were in mild correlation with age (r>0.5). There was significant difference between mean ages of patients with low bone mass for chronological age and normal bone densitometry values (p<0.05). There were 27, 36 and 28 patients in Group 1, Group 2 and Group 3, respectively. The difference between mean BMD values of these groups were statistically significant (p<0.05). The mean values of lumbar Z-scores of patients were -1.08 +/- 1.27, -1.42 +/- 1, -1.86 +/- 1.14, respectively for these three groups. Conclusion: Bone mineral densities of CD patients in childhood were lower in elder children at the time of diagnosis. This confirms the opinion that the diagnosis at earlier age results better treatment chance before bone mineral loss appears in CD patients.
Keywords: Celiac disease; osteoporosis; bone mineral density; age